A simplified approach to normalisation of piezocone penetration rate effects. Issue 7 (15th July 2019) - Schnaid, Fernando; Dienstmann, Gracieli; Odebrecht, Edgar; Maghous, Samir
Abstract : The influence of factors controlling the rate of penetration during piezocone tests (CPTU) is addressed in the present paper, including a critical appraisal of measurements adopted as input in existing dimensionless analysis. From a heuristic approach, a method is proposed to identify possible consolidation effects taking place during penetration using the velocity factor, V ¯ h . Defined as a direct function of probe size, d, penetration rate, v, and dissipation time, t 50, the dimensionless velocity factor V ¯ h is used to demonstrate that normalisation of cone penetration velocity is an important step for assessment of soil properties and for comparative performance of data from different geomaterials. An application is reported to illustrate the normalisation of measured data in soils within the permeability range from 10 −5 to 10 −8 m/s.